The sustainable enterprise fieldbook : building new bridges - Wirtenberg, Jeana; Russell, William G.,Ed; Lipsky, David,Ed; Kelley, Linda M.,Ed (Routledge, 2019)
With deep thought and inspiring examples, this updated book engages readers by increasing their understanding and awareness of what sustainability means conceptually, practically, personally, and professionally. It provides readers with the tools and techniques to improve the social, environmental, and economic performance of their organizations in both the short and long term. Since sustainability is not achieved in a siloed environment, everyone has a critical role to play on this journey.